Arboreal mammals inventory in Tapos area of gunung Gede Pangrango national park - Amin Indra Wahyuni; Ardian Khairiah; Bambang Mulyawan (UNIVERSITAS NEGERI PADANG, 2022)
Taman Nasional Gunung Gede Pangrango (TNGGP) is a mountainous tropical rain forest ecosystem area that has the potential natural resources of flora, fauna and ecosystems, so inventory is needed to know the existence of a various species and organism community structure in that habitat. This study was aimed to get arboreal mammal inventory data in Pengelolaan Taman Nasional (PTN) Tapos area and expected to provide scientific data that can be used as a reference for conservation efforts at PTN Tapos. The method used in this study is line transect in Cibayawak and Pasir Banteng track and the activity observation using focal animal sampling method and continued with data descriptive analysis. 5 species of mammal consist Ratufa bicolor, Tupaia javanica, Hylobates moloch, Trachypitecus auratus and Callociurus notatus species were found in this study. 5 mammal species found in Cibayawak track consist of 36 individuals while in Pasir Banteng track, 3 species mammal found consist of 11 individuals. High amount of mammal found in Cibayawak track caused by the availability of feed based on the finding of primate forage trees from species Ficus sp., feeding activity found from Ratufa bicolor and Tupaia javanica, and also availability of water sources in the form of river as water source and as well as a limiting factor.Pusat Taman Nasional (PTN) Tapos merupakan salah satu bidang pengelolaan di Taman Nasional Gunung Gede Pangrango (TNGGP) yang memiliki visi pengembangan konservasi sebagai pusat konservasi hutan hujan tropis yang sinergis dengan pembangunan wilayah dan masyarakat. Penelitian ini bertujuan untuk memperoleh data inventarisasi primata dan mamalia kecil di kawasan PTN Tapos. Metode yang digunakan adalah line transect di jalur cibayawak dan pasir banteng dan pengamatan perilaku dengan metode focal animal sampling dilanjutkan dengan analisis data secara deskriptif. Penelitian ini diharapkan dapat memberikan data sains yang dapat digunakan sebagai referensi untuk upaya konservasi di PTN Tapos. Dari penelitian ini ditemukan 5 spesies mamalia terdiri dari spesies Ratufa bicolor, Tupaia javanica, Hylobates moloch, Trachypitecus auratus dan Callociurus notatus. Pada jalur cibayawak ditemukan 5 spesies mamalia dengan jumlah mencapai 36 individu sedangkan pada jalur Pasir banteng ditemukan 3 spesies mamalia sejumlah 11 individu. Tingginya jumlah temuan mamalia di jalur cibayawak dikarenakan ketersediaan pakan yang lebih tinggi berdasarkan temuan pohon pakan primata dari spesies Ficus sp. serta aktivitas makan Ratufa bicolor dan Tupaia javanica.